Respuesta :

Answer:

I think it is -1

Step-by-step explanation:

Simplify the problem first.

Let's start with the numerator.

FYI, this, ^, means raised to the power of.

4^3 = 64

-12 + 2^2 = -12 +4 which equals -8

64/-8 = -8

Now simplify the denominator.

(2*3)^2 = 6^2 which equals 36.

-5*2*3 = -10*3 which equals -30

Then add the 2 to the end.

36 + (-30) + 2 = 6 + 2 which equals 8. This is the denominator.

Your fraction now is:

-8/8

Simplify this and you will get -1 as the simplest form.

Please forgive me if this is incorrect.

9514 1404 393

Answer:

  -1

Step-by-step explanation:

A suitable calculator can find the value for you.

  [tex]\dfrac{4^3/(-12+2^2)}{(2\times3)^2+(-5\times2\times3)+2}=\dfrac{64/(-12+4)}{6^2+(-5\times2\times3)+2}=\dfrac{64/(-12+4)}{36+(-5\times2\times3)+2}\\\\=\dfrac{64/(-8)}{36+(-30)+2}=\dfrac{-8}{6+2}=\boxed{-1}[/tex]

Ver imagen sqdancefan